Assessment of Peak Expiratory Flow Rate in school-going children in selected schools of Morang district, Nepal - Koirala, Namu; Kafle, Shyam Prasad; Pradhan, Uma; Subba, Dipty (Purbanchal University Health Journal, 2022)
<p style="box-sizing: border-box; line-height: 1.785rem; margin: 1.43rem 0px; color: rgba(0, 0, 0, 0.87); font-family: 'Noto Sans', -apple-system, BlinkMacSystemFont, 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction: Childhood bronchial asthma is an important public health problem in the world. Peak Expiratory Flow Rate (PEFR) can be used as a measurement of the ventilatory function of the lung in community settings. <p style="box-sizing: border-box; line-height: 1.785rem; margin: 1.43rem 0px; color: rgba(0, 0, 0, 0.87); font-family: 'Noto Sans', -apple-system, BlinkMacSystemFont, 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Objective: The objective of the study was to measure the PEFR of normal children and to study the correlation of PEFR with age, sex, Body Mass Index (BMI), and Body Surface Area (BSA) of school children from class 4-10, in selected schools of Province no.1, Nepal. Method: A quantitative, descriptive, cross-sectional study was done over 1 year. The sample consisted of 500 school-going children from Province no. 1, Nepal (studying from class 4-10) from 5 schools. A structured questionnaire was used for data collection which was validated with the consultation of experts. Children with medical illnesses were excluded. Height and weight were measured and the technique of measuring PEFR was explained and demonstrated to the subjects. Three acceptable forced expiratory measures were recorded with mini-Wright Flow meter and the one with the highest reading was taken as a representative value. <p style="box-sizing: border-box; line-height: 1.785rem; margin: 1.43rem 0px; color: rgba(0, 0, 0, 0.87); font-family: 'Noto Sans', -apple-system, BlinkMacSystemFont, 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Result: It was found that mean age (in years) was 12.6 ± 2.1 for male, 12.4 ± 2.1 for female, mean height (in cm) was 142.5 ± 13.8 for male, 136.6 ± 12.7 for female, mean weight (in kg) was 39.6 ± 10.6 for male, 37.2 ± 10.5 for female, Mean Body mass Index was 18.1 ± 2.8 for male, 18.5 ± 3.0 for female and Mean Body surface area was 1.24 ± 0.24 for male, 1.20 ± 0.20 for female. There was significant correlation of PEFR with age (r=0.711 for male, r=0.681 for female), height (r=0.821 for male, r=0.820 for female),weight (r=0.782 for male, r=0.732 for female), body mass index (r=0.342 for male, r= 0.340 for female) and body surface area (r=0.811 for male, r=0.723 for female). <p style="box-sizing: border-box; line-height: 1.785rem; margin: 1.43rem 0px 0px; color: rgba(0, 0, 0, 0.87); font-family: 'Noto Sans', -apple-system, BlinkMacSystemFont, 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion: In this study, the PEFR value ranged from 83 to 499 L/min, and a significant correlation of PEFR was found with age, height, weight, body mass index, and body surface area.